Ecclesiastical careers in Early Modern Spain: vocation or way of life? - Morgado García, Arturo (Cuadernos de Historia Moderna, 2021)
We try to analyze ecclesiastical careers in Early Modern Spain, determining the weight of the vocational factor, and focusing on the possible renunciations that the priesthood career could entail.